The Ionoregulatory Physiology of Freshwater-Adapted Mummichog (Fundulus Heteroclitus) - Patrick, Marjorie (My University, 1994)
This thesis examined the ionoregulatory physiology of freshwater-adapted mummichog (𝘍𝘶𝘯𝘥𝘶𝘭𝘶𝘴 𝘩𝘦𝘵𝘦𝘳𝘰𝘤𝘭𝘪𝘵𝘶𝘴) 𝘪𝘯 𝘷𝘪𝘷𝘰 and its interaction with acid-base regulation. Under control conditions (water [NaCl] ≈ 0.7-1 .0 mmol· L⁻¹, [Ca²⁺] ≈ 0.1 or 1.0 mmol· L⁻¹), Na⁺ turnover was vigorous with a positive Na⁺ balance maintained, whereas unidirectional Cl⁻ influx was virtually zero resulting in a slight negative Cl⁻ balance. Michaelis-Menten analysis revealed a low affinity, high capacity Na⁺ uptake mechanism that was independent of both Na⁺ efflux and ammonia excretion. Cl⁻ uptake started at higher water [NaCl] levels ( > 2 mmol • L⁻¹) but did not saturate within the freshwater [NaCl] range, indicating a completely different uptake mechanism, independent from Na⁺ influx. Using both internal and environmental manipulation, Na⁺ uptake was found not to be coupled to ammonia excretion. Instead, a link with acid excretion (Na⁺ /H⁺ exchange or Na⁺ channel/H⁺ -ATPase coupling) remains possible but could not be confirmed. There was no evidence for the presence of a Cl⁻/HC0₃⁻exchange mechanism in the gills. However, mummichog were capable of differentially manipulating Na⁺ and Cl⁻ efflux components as an additional response to an internal acid-base disturbance. This ability and the suggested Na⁺ uptake/acid excretion coupling indicate that mummichog resemble other freshwater fish in that an iono/acid-base relationship exists. In these studies, the use of the Strong lon Difference Theory as a means of assessing acid-base balance through the measurement of differential Na⁺ and Cl⁻ fluxes proved to be acceptable and practical alternative to the measurement of acid-base fluxes by traditional titration methodology. Finally, whole-body Ca²⁺ uptake was investigated using a recently developed technique for small fish. Ca²⁺ uptake by the mummichog involves a carrier-mediated step as revealed by saturation of uptake as external [Ca²⁺] increased. Inhibition of uptake by external La³⁺ but not Mg²⁺ suggested that apical Ca²⁺ channels are involved in the uptake process but are not voltage-gated. Chronic exposure to low Ca²⁺ water resulted in a stimulated Ca²⁺ uptake, most likely in response to depletion of internal Ca²⁺ levels whereas chronic exposure to high Ca²⁺ did not elicit any changes in uptake. This thesis revealed that the freshwater-adapted mummichog does share certain ionoregulatory qualities with other freshwater fish but at the same time possesses unique characteristics which may reflect its euryhaline nature
Ionoregulation of Freshwater-Adapted Fundulus Heteroclitus
Keywords: ionoregulation; freshwater; mummichog; fundulus